Cell-sorting centrifugal microfluidic chip with a flow rectifier. Issue 11 (30th April 2021) - Ma, Junyu; Wu, Yihui; Liu, Yongshun; Ji, Yuan; Yang, Mei; Zhu, Hongquan
Abstract : We propose herein a centrifugal microfluidic chip with a flow rectifier that transforms the centrifugal non-steady flow into locally steady flow with continuous flow for size-based cell sorting. Abstract : Centrifugal microfluidic chips offer rapid, highly integrable and simultaneous multi-channel microfluidic control without relying on external pressure pumps and pipelines. Current centrifugal microfluidic chips mainly separate particles of differing density based on the sedimentation method. However, in some biological cells, the volume difference is more notable than the density difference. In particular, cancer cells are generally larger than normal cells. The instability of particle velocity caused by the non-steady flow of the fluid in the centrifugal microfluidic chip leads to low separation purity of particles of different sizes. Thus, we propose herein a centrifugal microfluidic chip with a flow rectifier that transforms the centrifugal non-steady flow into locally steady flow with continuous flow. This chip resolves the problems caused by particle sedimentation in the sample chamber and non-steady flow and greatly improves the recovery ratio and separation purity of target particles. Therefore, it can be used to separate particles of differing size. The experimental results show that the chip can separate an equal-volume mixture of 25 μm and 12 μm polystyrene particles diluted 50 times with a ratio of 1 : 6 and obtain a recovery ratio and separation purity better than 95% for the 25 μm particles. In addition, rare tumour cells are separated from high-concentration white blood cells (ratio 1 : 25) with a recovery ratio of 90.4% ± 2.4% and separation purity of 83.0% ± 3.8%. In conclusion, this chip is promising for sorting of various biological cells and has significant potential for use in biomedical and clinical applications.